Music Reliefs from the Beethoven monument in Bonn: The imagination. Church music. The symphony. Dramatic music - Hähnel, Ernst Julius, 1811-1891 (sculptor):::Creator:::::::::::: (Beethovenhaus; Deutschen Photogravur A.-G.; Germany; Bonn; Siegburg, 2020)
Postcard with image of the four reliefs at the base of Hähnel's statue of Beethoven in Bonn